The USA lags behind other agricultural nations in banning harmful pesticides - Donley, Nathan (Environmental health, 2019)
The United States of America (USA), European Union (EU), Brazil and China are four of the largest agricultural producers and users of agricultural pesticides in the world. Comparing the inclination and ability of different regulatory agencies to ban or eliminate pesticides that have the most potential for harm to humans and the environment can provide a glimpse into the effectiveness of each nation's pesticide regulatory laws and oversight. The approval status of more than 500 agricultural pesticides was identified in the USA, EU, Brazil and China and compared between nations. The amount of pesticides that were used in the USA and banned in these other nations was compiled and linear regression was used to identify trends in use. There are 72, 17, and 11 pesticides approved for outdoor agricultural applications in the USA that are banned or in the process of complete phase out in the EU, Brazil, and China, respectively. Of the pesticides used in USA agriculture in 2016, 322 million pounds were of pesticides banned in the EU, 26 million pounds were of pesticides banned in Brazil and 40 million pounds were of pesticides banned in China. Pesticides banned in the EU account for more than a quarter of all agricultural pesticide use in the USA. The majority of pesticides banned in at least two of these three nations have not appreciably decreased in the USA over the last 25 years and almost all have stayed constant or increased over the last 10 years. Many pesticides still widely used in the USA, at the level of tens to hundreds of millions of pounds annually, have been banned or are being phased out in the EU, China and Brazil. Of the pesticides banned in at least two of these nations, many have been implicated in acute pesticide poisonings in the USA and some are further restricted by individual states. The United States Environmental Protection Agency (US EPA) has all but abandoned its use of non-voluntary cancellations in recent years, making pesticide cancellation in the USA largely an exercise that requires consent by the regulated industry.